2006
DOI: 10.1021/jp062004h
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Dielectric Function of Biotin-Capped Gold Nanoparticles via Signal Enhancement on Surface Plasmon Resonance

Abstract: Biotin-capped gold nanoparticles assembled on flat gold with volume fraction f are studied by surface plasmon resonance (SPR) spectroscopy and atomic force microscopy (AFM) in order to estimate the dielectric function of the gold nanoparticles based on the Maxwell-Garnett (MG) theory. The complex dielectric function (epsilon',epsilon'') of the spherical nanoparticles at three representative wavelengths in the vis-near-IR region, i.e., lambda = 543, 632.8, and 1152 nm, is estimated for a surface homogeneously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 49 publications
4
61
0
Order By: Relevance
“…By the experiment for the adsorption of biotin-capped gold nanoparticles on gold modified with streptavidin, we confirmed a good agreement between the theoretical calculation and experimental result up to f=0.1 on the surface homogeneously covered with well-dispersed particles (without aggregation) [19]. When the particles start aggregation at the high surface concentration, we could see the clear deviation from the theoretical prediction as a result of dipole coupling, which brought an additional enhancement to our SPR signals [20].…”
Section: Estimation Of Dielectric Function Based On Mg Theorysupporting
confidence: 79%
“…By the experiment for the adsorption of biotin-capped gold nanoparticles on gold modified with streptavidin, we confirmed a good agreement between the theoretical calculation and experimental result up to f=0.1 on the surface homogeneously covered with well-dispersed particles (without aggregation) [19]. When the particles start aggregation at the high surface concentration, we could see the clear deviation from the theoretical prediction as a result of dipole coupling, which brought an additional enhancement to our SPR signals [20].…”
Section: Estimation Of Dielectric Function Based On Mg Theorysupporting
confidence: 79%
“…[27] Additionally, when the particles have a strong plasmon absorption at the excitation wavelength, the SPR angle shifts to a large value. [28] In our case, with the decrease of the interparticle distance, the near-field coupling will happen, and the plasmon absorption band will shift to longer wavelength, and come closer to the excitation wavelength used in our SPR measurement, which results in the larger SPR angle shift and high sensitivity. When u SC surpasses 45.3%, reaches 52.3%, and increases up to 100%, the angle shift decreases greatly.…”
Section: Sensing With a Au/al 2 O 3 Nanocomposite Film-modified Spr Tmentioning
confidence: 76%
“…For example, for binary liquid mixtures with refractive indicies, n 1 , n 2 , and fill fraction, φ , the composite can be approximated as n mixed = n 1 φ + n 2 (1 − φ ), with more complex liquid mixing models like Weiner's relation and Heller's relation yielding negligible differences (Bhatia et al, 2002). For solid inclusions, the extension of the Maxwell-Garnett (MG) mixing rule (Garnett, 1904) by Garcıa et al (1999) has been shown effective, even when the particles are non-spherical and anisotropically clustered (Li et al, 2006). At present, PAME includes MG, with and without Garcia's extension, the Bruggeman equation (Bruggeman, 1935), the quasicrystalline approximation with coherent potential (Liu et al, 2011;Tsang et al, 1985), and various binary 4 Ferromagnetic nanoparticles do exist, and are have already been utilized in sensing applications (Pellegrini and Mattei, 2014) 5 Materials are supplied as is with no guarantee of accuracy: use at your own discretion.…”
Section: Composite Materialsmentioning
confidence: 99%
“…PAME currently supports nanospheres and nanospheres with shells; planned support for exotic particle morphologies is described in the Future Improvements section. Similar treatments of nanoparticle layers with effective media approximations have been successful (Li et al, 2006;Liu et al, 2011), even for non-spherical particles, and for ensembles of different sized particles (Battie et al, 2014). This is a salient difference between PAME, and numerical approaches like the boundary element method(BEM), discrete dipole approximation(DDA) and finite-difference timedomain(FDTD): PAME relies on mixing theories, and hence is constrained by any underlying assumptions of the mixing model.…”
Section: Nanomaterialsmentioning
confidence: 99%